One 2 Go Travel & Tour Web-Based Management System - Mohd Radzi, Nur Iffah Syamilah; MOHAMED, ROZLINI (Applied Information Technology And Computer Science, 2025)
The travel industry evolves with the integration of technology, but many small travel agencies still rely on manual methods that hinder efficiency and customer satisfaction. One 2 Go Travel & Tour, a travel agency based in Kulim, Kedah, currently uses platforms like WhatsApp and Facebook to handle customer inquiries, bookings, and package promotions. This approach leads to delays in responses, repetitive tasks, unorganized data storage, and difficulties in managing customer records, payment details, and booking histories. To address these challenges, this project proposes the development of a Web-Based Management System that centralizes operations and improves customer experience. The objectives are to design, develop, and test a system that allows administrators to manage bookings, payments and travel packages, while providing customers with a user-friendly platform to browse packages, compare prices, make bookings, process payments, and view their booking histories. The system is developed using the Prototype Model, with Laravel as the development framework and SQLite for database management. Key phases include requirements gathering, iterative prototype design, customer evaluation, and final implementation. The findings demonstrate that the system streamlines administrative processes, reduces response times, minimizes errors, and enhances operational efficiency. For customers, it offers a seamless self-service experience with real-time access to travel information, bookings, and payments. In conclusion, the One 2 Go Travel & Tour Web-Based Management System upgrades agency operations, improves customer satisfaction, and enables data-driven decision-making. Future enhancements may include multi-language support, social media integration, and advanced analytics to further expand functionality and reach.